Plane Symmetry Cosmology Model of Interacting Field in f(R, T) Theory. Issue 1 (2nd January 2022) - Pawar, D.D.; Mapari, R.V.
Abstract: We have explored a plane symmetric cosmological model in f ( R, T ) gravity. We have used an interacting field as a source of energy, as well as dark energy. In this case, the interacting field is simply a linear coupling between an electromagnetic field, a massless scalar field, and a charged perfect fluid. Four cases have been described 1) Perfect fluid, 2) Disordered radiation, 3) Dust fluid, and 4) Dark energy. We used the relationship between metric potential to solve field equations. By using equation of state, we observed the pressure and density profiles in various models. We also went over some cosmological and dynamical parameters in depth. Also, we discovered both negative and positive deceleration parameters in different time intervals, indicating the Universe's transition phase.